ОСОБЛИВОСТІ ЕКСПРЕСІЇ МАТРИЦЕЛЮЛЯРНІХ БІЛКІВ ПРИ МЕТАСТАТИЧНОМУ РАКУ МОЛОЧНОЇ ЗАЛОЗИ НА ТЛІ МЕТАБОЛІЧНОГО СИНДРОМУ - NEBORETS, A.D.; NIKOLAYENKO, S.I.; SMOLANKA, I.I.; KROTEVYCH, M.S.; MED, V.V.; GICHKA, S.G.; CHEKHUN, V.F. (PH Akademperiodyka, 2024)
Background. Metastatic breast cancer (mBCa) is one of the main causes of mortality among postmenopausal women with malignant neoplasms. Numerous studies indicate the feasibility of using bone matrix remodeling proteins to predict the BC course. Aim. To investigate the relationship between osteopontin (OPN) and osteonectin (ON) expression levels in tumor tissue of patients of menopausal age with primary mBCa (pmBCa) and metabolic syndrome (MetS) taking into account the clinicopathological features of the disease. Materials and Methods. The study included 54 menopausal patients with pmBCa, 23 from whom had manifestations of MetS, while 31 patients were without MetS. The expression of matricellular proteins (OPN and ON) was determined immunohistochemically. Results. In tumor tissue of patients with MetS and pmBCa of category N3, an increase in the level of OPN expression (H-Score of 265.6 ± 7.7, p < 0.05) was recorded along with a decrease in the expression level of ON (H-Score of 123.2 ± 7.7, p < 0.05). The invasive lobular pmBCa in patients with MetS was characterized by a significant decrease in the level of OPN expression ( H-Score of 219.4 ± 8.4) and an increase in ON expression (H-Score of 144.8 ± 7.5). In the patients with MetS, a significant decrease in ON expression (p < 0.05) was recorded in the tumor tissue of luminal A, luminal B, and Her2/neu subtypes ( H-Scores of 140.2 ± 7.8, 119.3 ± 10.2, and 110.0 ± 7.7, respectively). Among the cases of pmBCa with diagnosed metastatic liver disease, ON expression in tumor tissue was lower in patients with MetS (H-Score of 146.2±9.1). Conclusions. The obtained data demonstrated the relationship between the expression indicators of matricellular proteins in the pmBCa tissue and the degree of malignancy and indicated the prospects for further studies of their prognostic value in the presence of MetS.